Analisis Konsep Penjumlahan di Kelas 1 Sekolah Dasar - Neni Wulandari Oktavia Ningrum; Chandra Chandra; Salmaini Safitri Syam (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2025)
This article explores the significance of gaining a clear understanding of the topic concept addition as the main foundation in mathematical literacy. This study examines various pedagogical approaches in introducing the concept of addition to students, emphasizing the importance of conceptual understanding compared to procedural learning. Analysis of several learning methods shows that the use of manipulative objects, visual representations, and the application of real contexts significantly improve students' understanding of the idea behind addition. The results of the research also indicate that difficulties in understanding the concept of addition at the early stage of Learning may affect the progress of advanced mathematical abilities. This article concludes that a learning approach that emphasizes conceptual understanding of addition as a quantity combination operation will establish a strong basis for the advancement of students' mathematical abilities in the future.